Informe Pasantía de Investigación: Prospectiva de las Industrias Culturales en Bogotá, Sector Editorial (2022)
The objective is to have a prospective of the cultural and creative industries, as well as the orange economy and the publishing industries of different countries such as Latin American, European and of course at the national level. In orange economy we will see the five orange reports and other articles related to this industry. We will allude to everything related to the publishing houses of Bogotá, the publishing houses of Latin America and the publishing houses of Europe and from the visit to the Bogotá Book Fair we will present an extensive photographic record of what was captured in the event